This is a Bernoulli differential equation.
"\\frac{dy}{dx}= \\frac{2y^2}{x^2}+\\frac{3y}{x}"
Let's divide both sides by "\\,-y^2" "\\,"
"-\\frac{dy}{y^2dx}= -\\frac{2}{x^2}-\\frac{3}{xy}"
Using the substitution "v=y^{-1}" , "v'=-\\frac{y'}{y^2}" will lead us to "\\,"
"v'=-\\frac{2}{x^2}-\\frac{3v}{x}"
This is a first-order linear equation which can be solved using an integrating factor "\\,"
"M=e^{\\int\\frac{3}{x}dx}=e^{3\\ln x}=x^3"
Multiplying both sides by M we get "\\,"
"x^3v'+3x^2v=-2x\\\\"
"(x^3v)'=-2x\\\\"
"x^3v=-x^2+C"
"v=\\frac{C-x^2}{x^3}\\\\"
Hence "\\,"
"y=\\frac{1}{v}=\\frac{x^3}{C-x^2}"
Comments
Leave a comment